2000
DOI: 10.1038/sj.leu.2401673
|View full text |Cite
|
Sign up to set email alerts
|

Individualized methotrexate dosing in children with relapsed acute lymphoblastic leukemia

Abstract: Although high-dose methotrexate has been extensively studied in children with newly diagnosed acute lymphoblastic leukemia (ALL), there are fewer data in children with relapsed ALL, many of whom have been heavily pretreated and have subclinical kidney dysfunction. We characterized the pharmacokinetics of adaptively controlled methotrexate given as a 24-h infusion during consolidation therapy in 24 children with relapsed ALL. To achieve the target steady-state concentration of 65 M, dosage adjustments were requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…This is in agreement with the sex difference observed in the pharmacokinetics of several known BCRP substrates in humans. Significantly higher plasma clearance was noted in men compared with women for topotecan (Gallo et al, 2000;Loos et al, 2003), methotrexate (Godfrey et al, 1998;Wall et al, 2000), doxorubicin (Dobbs et al, 1995), and epirubicin (Wade et al, 1992). This sex difference can thus have important pharmacological and toxicological implications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with the sex difference observed in the pharmacokinetics of several known BCRP substrates in humans. Significantly higher plasma clearance was noted in men compared with women for topotecan (Gallo et al, 2000;Loos et al, 2003), methotrexate (Godfrey et al, 1998;Wall et al, 2000), doxorubicin (Dobbs et al, 1995), and epirubicin (Wade et al, 1992). This sex difference can thus have important pharmacological and toxicological implications.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate dosing may, for example, lead to suboptimal treatment in some patients and expose others to the risk of unacceptable toxicity. For methotrexate, it has been suggested that higher effective exposure to the drug because of lower clearance in women could contribute to their better chemotherapeutic overall outcome (Wall et al, 2000). Along the same lines, it has been suggested that women are at higher risk for methotrexate toxicity; therefore, lower dosing may be appropriate in female patients (Godfrey et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Host factors such as polymorphisms of drug metabolizing genes are also likely to impact the apoptotic response since these variables would influence the timing and magnitude of the initial apoptotic stimulus. [40][41][42][43][44] However, despite any potential differences in drug pharmacokinetics, the apoptotic response was initiated in all patients with three exceptions since blast counts fell significantly within 24 h following the start of treatment. Thus the character of the apoptotic pathway could be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…All specimens were collected prospectively for pharmacokinetic analysis, and some results have been reported previously. 17,[24][25][26] The population pharmacokinetics were determined by using the 2-stage approach. 27 First, the pharmacokinetic parameters for each individual were estimated for each of the courses by using compartmental analysis.…”
Section: Pharmacokineticsmentioning
confidence: 99%